Interventions to improve oral vaccine performance: a systematic review and meta-analysis - Church,JA; Parker,EP; Kirkpatrick,BD; Grassly,NC; Prendergast,AJ (Lancet Infectious Diseases, 2019)
BackgroundOral vaccines underperform in low-income and middle-income countries compared with in high-income countries. Whether interventions can improve oral vaccine performance is uncertain.MethodsWe did a systematic review and meta-analysis of interventions designed to increase oral vaccine efficacy or immunogenicity. We searched Ovid-MEDLINE and Embase for trials published until Oct 23, 2017. Inclusion criteria for meta-analysis were two or more studies per intervention category and available seroconversion data. We did random-effects meta-analyses to produce summary relative risk (RR) estimates. This study is registered with PROSPERO (CRD42017060608).FindingsOf 2843 studies identified, 87 were eligible for qualitative synthesis and 66 for meta-analysis. 22 different interventions were assessed for oral poliovirus vaccine (OPV), oral rotavirus vaccine (RVV), oral cholera vaccine (OCV), and oral typhoid vaccines. There was generally high heterogeneity. Seroconversion to RVV was significantly increased by delaying the first RVV dose by 4 weeks (RR 1·37, 95% CI 1·16–1·62) and OPV seroconversion was increased with monovalent or bivalent OPV compared with trivalent OPV (RR 1·51, 95% CI 1·20–1·91). There was some evidence that separating RVV and OPV increased RVV seroconversion (RR 1·21, 95% CI 1·00–1·47) and that higher vaccine inoculum improved OCV seroconversion (RR 1·12, 95% CI 1·00–1·26). There was no evidence of effect for anthelmintics, antibiotics, probiotics, zinc, vitamin A, withholding breastfeeding, extra doses, or vaccine buffering.InterpretationMost strategies did not improve oral vaccine performance. Delaying RVV and reducing OPV valence should be considered within immunisation programmes to reduce global enteric disease. New strategies to address the gap in oral vaccine efficacy are urgently required.